The Clinical Utility of Optical Genome Mapping for the Assessment of Genomic Aberrations in Acute Lymphoblastic Leukemia - Lühmann, Jonathan Lukas; Stelter, Marie; Wolter, Marie; Kater, Josephine; Lentes, Jana; Bergmann, Anke Katharina; Schieck, Maximilian; Göhring, Gudrun; Möricke, Anja; Cario, Gunnar; Žaliová, Markéta; Schrappe, Martin; et al. (Cancers, 2021)
Acute lymphoblastic leukemia (ALL) is the most prevalent type of cancer occurring in children. ALL is characterized by structural and numeric genomic aberrations that strongly correlate with prognosis and clinical outcome. Usually, a combination of cyto- and molecular genetic methods (karyotyping, array-CGH, FISH, RT-PCR, RNA-Seq) is needed to identify all aberrations relevant for risk stratification. We investigated the feasibility of optical genome mapping (OGM), a DNA-based method, to detect these aberrations in an all-in-one approach. As proof of principle, twelve pediatric ALL samples were analyzed by OGM, and results were validated by comparing OGM data to results obtained from routine diagnostics. All genomic aberrations including translocations (e.g., dic(9;12)), aneuploidies (e.g., high hyperdiploidy) and copy number variations (e.g., IKZF1, PAX5) known from other techniques were also detected by OGM. Moreover, OGM was superior to well-established techniques for resolution of the more complex structure of a translocation t(12;21) and had a higher sensitivity for detection of copy number alterations. Importantly, a new and unknown gene fusion of JAK2 and NPAT due to a translocation t(9;11) was detected. We demonstrate the feasibility of OGM to detect well-established as well as new putative prognostic markers in an all-in-one approach in ALL. We hope that these limited results will be confirmed with testing of more samples in the future.
Keywords: gene fusion; molecular karyotyping; risk assessment; ALL; copy number alteration; prognostic marker; Optical Genome Mapping